Pengaruh Konsep Vernakular Jaga Satru Terhadap Ruang Kawasan Permukiman di Desa Adat Tenganan Pegeringsingan - I Made Oka Handara made; Dwita Hadi Rahmi dwita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Tenganan Pegeringsingan Traditional Village is part or belongs to three Bali Aga Villages located in the province of Bali. The values and traditions of their ancestors are strongly maintained by the residents of the Tenganan Pegeringsingan Traditional Village. The location of this village is in Manggis District, Karangasem Regency. Tenganan Pegeringsingan Traditional Village has the concept of Jaga Satru or a vernacular concept that only exists in Tenganan Village, that concept is a concept passed down from generation to generation by the local community which was obtained from Dewa Indra as the highest God who is highly trusted by the people of Tenganan Village. The concept of Jaga Satru is the concept of the form of a residential area shaped like a defense "barrack", besides that this concept also applies the form of community housing with the Mahulu ka Tengah concept or orientation towards the holy direction inward with 2 doors in front and behind the house in every existing house. . The purpose of this study is to see the spatial relationship of the residential area in the Tenganan Pegeringsingan Traditional Village with the Jaga Satru concept or the vernacular concept used in the village. This study uses inductive qualitative data collection through observation of secondary data and interviews in the field. The results of the identification of the link between the Jaga Satru concept and the change in the spatial form of the residential area in the Tenganan Pegeringsingan Traditional Village are not significant. In other words, the vernacular concept of Jaga Satru that is used and applied greatly affects the least changes that occur in the spatial form of the residential area as a whole in the Tenganan Pegeringsingan Traditional Village.